PARADIGMA HUMANISME PAULO FREIRE DALAM TRANSFORMASI MANAJEMEN PENDIDIKAN ABAD 21: ANALISIS KRITIS PRAKTIK MANAJEMEN PENDIDIKAN SAAT INI - Wulan Widaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article analyzes educational management practices in 21st-century Indonesia through the lens of Paulo Freire’s dialogical humanism. The study identifies that the dominance of bureaucratic and technocratic paradigms in school management has generated various disparities, such as teacher alienation, pseudo-participation, the digital divide, and the dehumanization of educational processes. Through multiple case studies in six secondary schools, it was found that spaces for dialogue, critical reflection, and transformative action remain highly limited due to the strong influence of administrative compliance and hierarchical culture. However, there is evidence that integrating Freire’s principles—dialogue, conscientização, praxis, and liberation—can foster a transformation of educational management into a more participatory, inclusive, and emancipatory model. The article recommends the need for administrative reform, strengthening reflective capacities, and utilizing local values as well as digital technologies to realize an educational management approach that is humanistic and relevant to the needs of the 21st century.